2019
DOI: 10.1186/s42834-019-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

The bio-mechanical properties of coco wood applied with Neem extracts: a potential preservative for sustainable building in Marinduque, Philippines

Abstract: The purpose of this study was to develop an organic wood preservative from the liquid extract of Neem tree (Azadirachta indica). This product has the potential in controlling the fast deterioration of coco wood by extracting liquid from fruits with seeds and leaves of Neem tree. Effectiveness as wood preservative was investigated for termite repellency, water absorption, and tangential swelling following American Society for Testing and Materials methods such as D-3345–74, D-4442-92, and D-4446-06, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Temiz et al (2013) reported higher swelling (tangential plane) of Arundo donax bio-oil treated samples than control. The increasing tangential and radial swelling with increased extract concentrations are in line with the finding of Shuib (2011), Okon (2014, Bossu et al (2016), andNey et al (2019). The extracts of L. camara (E1 and E2) reduced the shrinkage values in tangential as well as radial direction with an increase in extract concentration representing reduction improvement of 20-42%; E1, 10-39%; E2 in the tangential direction, and 2-39%; E1, 7-34%; E2 in the radial direction.…”
Section: Dimensional Stabilitysupporting
confidence: 89%
“…Temiz et al (2013) reported higher swelling (tangential plane) of Arundo donax bio-oil treated samples than control. The increasing tangential and radial swelling with increased extract concentrations are in line with the finding of Shuib (2011), Okon (2014, Bossu et al (2016), andNey et al (2019). The extracts of L. camara (E1 and E2) reduced the shrinkage values in tangential as well as radial direction with an increase in extract concentration representing reduction improvement of 20-42%; E1, 10-39%; E2 in the tangential direction, and 2-39%; E1, 7-34%; E2 in the radial direction.…”
Section: Dimensional Stabilitysupporting
confidence: 89%
“…Leaves were collected from the same tree into clean, dry, labeled plastic bags. Samples were kept frozen at -80 °C until the time of their use [ 60 ]. A taxonomist authenticated the plant at Medicinal and Aromatic Plants and Traditional Medicine Research Institute (MAPRI) National Center for Research, Khartoum, Sudan.…”
Section: Methodsmentioning
confidence: 99%
“…Another approach to protecting coconut wood is through the use of natural extracts. A study [40] examined the effectiveness of a natural extract derived from neem leaves on coconut wood. The results showed that the extract significantly inhibited the growth of fungi and termites, indicating its potential as a natural preservative for coconut wood.…”
Section: Durability and Protection Of Coconut Woodmentioning
confidence: 99%